AVALIAÇÃO PÓS-OCUPAÇÃO E A PERCEPÇÃO ESPACIAL ESTUDANTIL: UM CASO DE ESTUDO EM PÁTIOS DE ESCOLA PÚBLICA DE ENSINO EM PALMITINHO, RS, BRASIL - Rech, Gracielle Rodrigues da Fonseca; Valle, ângela do; Lermen, Bruna Cristina (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Starting from the theme of schoolyard architecture, the research aimed to analyze the courtyard of public elementary schools, according to the point of view of the students. The article presents the evaluation carried out at a public educational institution located in the city of Palmitinho, Rio Grande do Sul, with emphasis on the instruments of analysis applied: cognitive map and poem of desires. The purpose of the investigation is to understand the relations of use and appropriation of these spaces, ascertaining the quality of the free areas and built environment. The participation of users showed up fundamental, once from the same one can identify suggestions for architectural projects that aim spaces of quality and favorable to users.